ЕКСПЕРИМЕНТАЛЬНА МОДЕЛЬ "Я” КОНЦЕПЦІЇ МОЛОДШОГО ШКОЛЯРА В КОНТЕКСТІ ОСОБИСТІСНО- ОРІЄНТОВАНОГО НАВЧАННЯ (Педагогіка вищої та середньої школи, 2022)
The developinq o f “j-Conseption ” in the schools conditions: kinder-qarden, primary - school, needs to be happened little by little depends on the schools laws and inculcation them in school culture, in school space.“J-conseption”, self-conscions, kinder-qarden, elementaryschool and cognitive componet.